Topiramate and Vitamin E Modulate the Electroencephalographic Records, Brain Microsomal and Blood Antioxidant Redox System in Pentylentetrazol-Induced Seizure of Rats - Naziroglu, Mustafa; Kutluhan, Sueleyman; Uguz, Abdulhadi Cihangir; Celik, Oemer; Bal, Ramazan; Butterworth, Peter J. (Springer, 2009)
We investigated the effects of vitamin E and topiramate (TPM) administrations on pentylentetrazol (PTZ)-induced blood and brain toxicity in rats. Forty rats were randomly divided into five equal groups. The first and second groups were used for the control and PTZ groups, respectively. Fifty or 100 mg TPM were administered to rats constituting the third and fourth groups for 7 days, respectively. The TPM and vitamin E combination was given to animals in the fifth group. At the end of 7 days, all groups except the first received a single dose of PTZ. Blood and brain samples were taken at 3 hrs after PTZ administration. Lipid peroxidation levels of plasma, erythrocyte, brain cortex and brain microsomal fraction; nitric oxide levels of serum; and the number of spikes and epileptiform discharges of the EEG were increased by PTZ administration. Plasma and brain vitamin E concentration, erythrocyte glutathione peroxidase (GSH-Px) activity and latency to first spike of the EEG were decreased by PTZ. Plasma lipid peroxidation levels in the third group and plasma and erythrocyte lipid peroxidation levels in the fifth group were decreased compared to the second group, whereas brain vitamin C, vitamin E, erythrocyte GSH-Px and reduced glutathione (GSH) values increased in the fifth group. Brain microsomal GSH levels and EEG records in the third, fourth and fifth groups were restored by the TPM and vitamin E treatment. In conclusion, TPM and vitamin E seems to have protective effects on PTZ-induced blood and brain toxicity by inhibiting free radicals and supporting the antioxidant redox system.
Keywords: Topiramate; Antioxidant; Oxidative stress; Brain; Erythrocyte; EEG record